Sintesis dan Karakterisasi Adsorben Lempung Terimpregnasi Oleh 3-merkapto-1,2,4-triazol (trzsh) - Fahmiati, Fahmiati (Jurnal Progres Kimia Sains, 2011)
Impregnation of clay is one of method to increase the adsorption capacity. Synthesisand characterization of clay impregnated 3-mercapto-1,2,4-triazole (TRZSH) has beencarried out. Functional groups of clay was characterized by infrared spectrophotometry whileBET test was performed to determine its specific surface area and porosity. Results showedthat clay impregnated TRZSH comprises silanol (Si-OH), siloksan (Si-O-Si), C-N, C=N, andSH. Spesific surface area of clay impregnated TRZSH of 184.04 m2/g. Such it has porosityvolume and radius of porosity of 123.902 x 10-3 cm/g and 134.672 A, respectively.